Pengaruh Tridharma Perguruan Tinggi terhadap Kinerja Dosen Milenial di Perguruan Tinggi Jakarta - Petrus P.F. Titirloloby; John Tampil Purba; Dylmon Hidayat; Hendra Achmadi (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to analyze the influence of tridharma perguruan tinggi on the performance of millennial lecturers. A quantitative approach was employed using a survey method involving 385 millennial lecturers from 30 universities under LLDIKTI Region III Jakarta, selected through cluster random sampling. Data were collected using a structured questionnaire that had undergone validity and reliability testing. Data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The outer model test results indicate that all indicators have loading factor values above 0.70 and AVE values greater than 0.5, confirming convergent validity. The reliability test using Composite Reliability yielded values above 0.962, and Cronbach's Alpha exceeded 0.951, indicating strong internal consistency. The results show that tridharma perguruan tinggi have significant effects on lecturer performance. This research provides implications for human resource development in higher education institutions, particularly in nurturing adaptive and productive young lecturers.